Pelatihan Peningkatan Pengetahuan dalam Pembuatan Beras – Kencur (Instant) sebagai Ninuman Kesehatan pada Masyarakat di Desa Singasari, Kecamatan Jonggol, Jawa Barat: Pengabdian - Sri Irtawidjajanti; Lillis Jubaedah; Jenny Sista Siregar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Singasari Village (Jonggol-West Java) which is the largest rice producing village, and won the 1st place in the provincial food masterpiece in 2024. Local resources have not been utilized, besides being a staple food. The training participants are students and housewives. The objectives of the training are: a. Providing real contributions to village residents, by utilizing local resources, b. Utilization of rice and kencur as health drinks, starting with providing knowledge about traditional (health) drinks that can be stored for a long time so that they can become products that have economic sales value, and c. Demonstrating the manufacture of instant health drinks. The pretest results (initial knowledge) owned by 13 extension participants were 59.9%. The posttest results (final knowledge & observations after seeing the demonstration) got 98.5%. The posttest results related to the delivery of material and demonstrations that were easy to understand, the presence of a guidebook for participants made it easier for participants to understand the process & follow the training, and became an inspiration to utilize instant kencur rice for health drinks.